SENYUM DALAM UNGKAP KARYA SENI LUKIS - AGUNG BUDIMAN, YAsrul Sami, S.Sn., M.Sn., Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2018)
The purpose of the creation of this work is to present a painting byvisualizing a smile in the expression of painting with the expressioniststyle. For the method of creation, the author uses five stages of preparation,elaboration, synthesis, concept realization and completion stage. In thecreation of the work, the author uses acrylic paint on canvas with a palletsweep technique. The style used is the expressionist style that tends to usestriking colors and shapes that begin to distort. Ten works that the authorspresent represent the theme that the author lift, contains problems relatedto the smile, contains about the phenomenon that occurs around the life ofwriters from the lower class to the government bureaucracy which willaffect the self and the general public. The 10 works are: 1) Tense, 2) SmileOff, 3) Ministry, 4) Temptation, 5) Smile in Canda, 6) Smile, 7) BrotherSmile, 8) Selfi, 9) Capture Moment, and 10) The Power Of Smile.Kata Kunci: Senyum, Seni Lukis, Ekspresionis.